Knowledge Management and Learning Organizations Advocacy for Integration - Isa, Mhd Rudayn (2009)
This new era that we are living in now has enforced different rules for competition among organizations and across all industries. Competition is intensifying and the markets are changing in nature in a rising speed. All this is happening while the world is becoming flat day after day with the help of the major characteristic of this new era – the quick transmitting of information. This is why this new era was called the ‘Information age’.